Characterisation of the Trichinella spiralis deubiquitinating enzyme, TsUCH37, an evolutionarily conserved proteasome interaction partner. - Rhiannon R White; Sachiko Miyata; Eliseo Papa; Eric Spooner; Kleoniki Gounaris; Murray E Selkirk; Katerina Artavanis-Tsakonas (Public Library of Science (PLoS), 2011)
Trichinella spiralis is a zoonotic parasitic nematode that causes trichinellosis, a disease that has been identified on all continents except Antarctica. During chronic infection, T. spiralis larvae infect skeletal myofibres, severely disrupting their differentiation state.An activity-based probe, HA-Ub-VME, was used to identify deubiquitinating enzyme (DUB) activity in lysate of T. spiralis L1 larvae. Results were analysed by immuno-blot and immuno-precipitation, identifying a number of potential DUBs. Immuno-precipitated proteins were subjected to LC/MS/MS, yielding peptides with sequence homology to 5 conserved human DUBs: UCH-L5, UCH-L3, HAUSP, OTU 6B and Ataxin-3. The predicted gene encoding the putative UCH-L5 homologue, TsUCH37, was cloned and recombinant protein was expressed and purified. The deubiquitinating activity of this enzyme was verified by Ub-AMC assay. Co-precipitation of recombinant TsUCH37 showed that the protein associates with putative T. spiralis proteasome components, including the yeast Rpn13 homologue ADRM1. In addition, the UCH inhibitor LDN-57444 exhibited specific inhibition of recombinant TsUCH37 and reduced the viability of cultured L1 larvae.This study reports the identification of the first T. spiralis DUB, a cysteine protease that is putatively orthologous to the human protein, hUCH-L5. Results suggest that the interaction of this protein with the proteasome has been conserved throughout evolution. We show potential for the use of inhibitor compounds to elucidate the role of UCH enzymes in T. spiralis infection and their investigation as therapeutic targets for trichinellosis.